Buluh Betong for the production of Peeled Bamboo-Fiberglass Composite (PBFC) / Mohd Aminuddin Che Haron … [et al.] - Che Haron, Mohd Aminuddin; Muhammed, Suhaimi; Saleh, Abdul Hamid; Mohd Hassan, Nurul Husna; Abdul Karim, Siti Rafedah (Research Innovation Business Unit, 2014)
Bamboo is considered as an environmentally and eco-friendly material compared to hardwood. Currently, the utilization of bamboo veneer is becoming increasingly important due to fact that bamboo veneer is demanded for many modern designs. The alternate layers of bamboo veneer (3 and 5 layers) were combined with fibreglass by using Epoxy resin (mixed with 2% hardener) as bonding agent to produce peeled bamboo fibreglass composite (PBFC) at different press pressures. Composite panels produced were assessed for the mechanical properties such as Modulus of elasticity (MOE) and Modulus of Rupture (MOR) in accordance with the European Standard (EN 310). Results revealed that mechanical strength of board improved with increasing pressure and the 3-layered panel was more flexible (>MOE) than the 5-layered panel. In term of dimensional stability, composite having 5-layered panel exhibited much better results. Water absorption and thickness swelling were lesser for 5-layered panel when higher press pressure used. Such findings revealed that bamboo veneer from Buluh betong possesses great potential as raw material for the manufacture of bio-composite products.